NATIONAL LANGUAGE DILEMMA AND ITS POTENTIAL ROLE IN NATION BUILDING: ACADEMICIANSâ€™ PERCEPTION IN PAKISTAN - BEGUM, TAHIRA (LINGUISTICA, 2021)
Pakistan inherits a multilingual heritage. Along with Urdu, 70 different languages are spoken.Â The 1973 Constitution officially recognizes Urdu as Pakistan's only national language. Till today, the adoption and promotion of Urdu as a medium of educational instruction has remained a point of controversy. Existing research lacks the voice of academicians on the issue. Present investigation focused on the voice of 100 university professors selected randomly. Part of PhD research, data was gathered using a standardized Likert Summative Ranking Scale. Data analysis revealed that there is a highly significant positive relationship (p = 0.000) between use of national language and nation-building. This means, academicians across Pakistani universities strongly believe in the use of national language in all walks of life to realize the dreams of the nation building. It will help to achieve socio-cultural, developmental, strategic, academic and identity goals amicably.